A multi-trait targeted genotype selection approach for screening drought tolerance in teosinte–maize hybrids - Jaishreepriyanka, R; Ravikesavan, R; Iyanar, K; Uma, D; Senthil, N (Plant Science Today, 2024)
Drought tolerance is a complex characteristic and screening based on multiple traits rather than direct selection indices would result in more efficient selection. The study aims to select hybrids under optimal and water deficit conditions to achieve genetic gains in yield traits without compromising the other secondary traits viz., anthesis-silking interval, leaf chlorophyll content, delayed leaf rolling and leaf senescence, relative water content, and ROS scavenging using the multi-trait genotype ideotype distance index. The 30 teosinte-maize hybrids along with four checks were evaluated for two classes of traits: 16 morphometric and 14 physiological and biochemical traits, under well-watered (WW) and water-stress (WS) environments. Significant variations among the genotypes were observed for most traits and the presence of moderate to high heritability for most traits suggests direct selection for improvement of those traits. Significant correlation of the traits with yield and intercorrelations between traits indicate the advantage of indirect selection based on secondary traits. By assuming a selection intensity of 15% and equal weightage to all the traits, five genotypes were selected based on the MGIDI under each class of traits and in each environment. The genotypes viz. G19, G20, and G29 were commonly selected across both environments. The selection led to desired positive and negative selection gains for most of the traits studied and resulted in high positive gains for single plant yield of 35.6% under WW and 69.3% under WS. The strength and weakness plots effectively present the advantages and limitations of the selected genotypes under each environment. The multi-trait-based selection approach is an effective tool for selecting genotypes and designing breeding strategies for stress breeding.